Preliminary Study on Laccase-Catalyzed Oxidative Transformation of Anethole: Evidence from GC-MS Analysis - Rahmah, Siti Zainatur; Pongpatrakant, Wimonnan (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research was conducted with the aim of synthesizing anethole dimers using the laccase enzyme biocatalyst. Methodology: In this study, anise oil containing 90% anethole, laccase enzyme as a biocatalyst, and hydroquinone as a mediator were used. The laccase enzyme used was isolated from white oyster mushroom (Pleurotus ostreatus) which has an activity of 712.758 U/L. The anethole dimer formation reaction was carried out in a biphasic medium (ethyl acetate: phosphate buffer = 4:1) which was carried out for 24 hours and 48 hours. The reaction results were then extracted with ethyl acetate and produced a thick brownish liquid with a more intense color intensity in the 48-hour reaction. Main Findings: Comparison of the GC test results on anise oil, 24-hour reaction, and 48-hour reaction showed an increase in peaks and changes in peak height in the 48-hour reaction. Anethole and p-anisaldehyde compounds had a smaller % area than in the 24-hour reaction. It is suspected that the 48-hour reaction produced a new compound derived from the oxidation reaction, namely caryophyllene oxide, but the compound that is the anethole dimer has not been identified. Novelty/Originality of this study: This study introduces a biocatalytic approach for anethole transformation using laccase from Pleurotus ostreatus, integrating mechanistic insights with product characterization. It reveals the limited reactivity of anethole under laccase catalysis while identifying alternative oxidation pathways, such as caryophyllene oxide formation. These findings advance understanding of substrate specificity and expand knowledge of laccase-mediated transformations in non-phenolic systems.